Reimagining Hospital Design Using the Metaverse: A Prospective Study of Virtual Health Applications - Mansour Abdo Ahmed Alsaadi, (International Journal of Computers and Informatics, 2024)
This study aims to reimagine hospital design using the metaverse, by exploring the potential applications of virtual health in improving healthcare services, patient experience, and reducing operational costs. The quantitative approach was followed in this study, where data was collected from a sample of 170 individuals. The results showed that the metaverse contributes significantly to improving healthcare services provided to patients, enhancing their experience within hospitals, and reducing operational costs through virtual reality technologies. The results also emphasized the importance of integrating the metaverse into training medical personnel and improving the efficiency of health management. One of the most important recommendations that emerged from the study is the need to integrate the metaverse into medical training and improve the patient experience, in addition to the need to explore prospects for reducing operational costs and promoting research in this field.
Keywords: Metaverse; hospital design; virtual health; improving health services; reducing operational costs